Comparison of flexible ureteroscopy with flexible and navigable suction ureteral access sheath and mini-percutaneous nephrolithotripsy for the treatment of impacted upper ureteral stones: a retrospective study - Tang, Haiyang; Che, Yulong; Wu, Zhanpeng; Yuan, Fangchao; Liu, Jiayu; Li, Jie (Frontiers in Surgery, 2025)
Background and objectiveThe treatment of impacted upper ureteral stones remains a significant challenge for urologists. Standard treatment protocols often favor Mini-Percutaneous Nephrolithotripsy (Mini-PCNL). It has been supposed to be associated with a higher stone clearance rate and a lower incidence of ureteral stricture compared to Flexible Ureteroscopy (FURS). Recently, FURS with flexible and navigable suction ureteral access sheath (FANS) has emerged as a promising alternative. The aim of this study was to compare the efficacy and safety of the FURS with FANS and Mini-PCNL for treating the impacted upper ureteral stones.MethodA retrospective study of 80 patients treated with FURS with FANS (Group A, n = 43) or Mini-PCNL (Group B, n = 37) was conducted in our center (from June 2023 to August 2024). Primary outcomes included stone-free rate (SFR), hemoglobin drop, hospital stay, and complications (Clavien-Dindo classification) in 3 months.ResultsBoth groups achieved comparable SFR (90.7% vs. 83.78%, P = 0.351). Group A had significantly lower hemoglobin drop (3.65 ± 8.39 vs. 7.89 ± 9.39 g/L, P = 0.036) and shorter hospital stays (1.79 ± 1.08 vs. 3.81 ± 1.37 days, P < 0.001). Complication rates were similar, but Group A had a higher rate of second-stage operation (18.6% vs. 8.1%, P = 0.174) and neither group required reoperation for ureteral stricture or rupture at 3 months post-surgery.ConclusionFURS with FANS is a safe and effective alternative to Mini-PCNL for impacted upper ureteral stones larger than 10 mm, offering shorter recovery times and lower bleeding. However, its higher second-stage operation rate necessitates further investigation.